Study of left-turn-green-arrow (ltga) traffic scheme at signalised junctions - Seet, Qiu Yiong. (2010)
The Land Transport Authority of Singapore (LTA) has implemented the traffic control Left-Turn-Green-Arrow (LTGA) at signalised junctions since 1996 to improve the conditions of the left-turning traffic. To date, there are many junctions with LTGA all over Singapore and the Authority may introduce such control to more junctions in future.